Model for self-polarization and motility of keratocyte fragments - Ziebert, Falko; Swaminathan, Sumanth; Aranson, Igor S. (Interface, 2012)
Computational modelling of cell motility on substrates is a formidable challenge; - regulatory pathways are intertwined and forces that influence cell motion are not - fully quantified. Additional challenges arise from the need to describe a moving deformable - ...
Published online 19/10/2011
Gesehen am 27.09.2022